Necrotic sarcoid granulomatosis – a late stage of nodular sarcoidosis or an independent disease? Analysis of a clinical case - E. A. Galushko; E. V. Pozhidaev; S. G. Radenska-Lopovok; A. V. Gordeev; M. V. Shaligina; A. V. Alekseeva; M. A. Sedelnikova (Научно-практическая ревматология)
The aim of this article was an attempt to answer the question: is necrotizing sarcoid granulomatosis a late stage of nodular sarcoidosis or an independent disease? In order to better understand the designated topic, as part of the description of the clinical case, a differential diagnosis of a number of granulomatous diseases with vasculitis was carried out. The main emphasis was placed on the accurate interpretation of pathomorphological features in each individual case.